FACTORS INFLUENCING ATTRITION IN 35 ALZHEIMER'S DISEASE CENTERS ACROSS THE UNITED STATES: A LONGITUDINAL EXAMINATION OF THE NATIONAL ALZHEIMER'S COORDINATING CENTER'S UNIFORM DATA SET. (11th November 2018) - Burke, S L; Hu, T; Fava, N M; Duara, R; O'Driscoll, J; Alvarez, D
Abstract: Factors associated with attrition were examined in the National Alzheimer's Coordinating Center (NACC) Uniform Data Set (UDS): a repository of observations of older adults spanning 11 years. A secondary data analysis, examining four subsamples of the NACC UDS, was conducted using survival analysis, including the full sample (n=30, 433), the full sample excluding participants who died (n=24, 231), participants with complete MRI data (n=1, 104), and participants with MRI data excluding those who died (n=947). A higher clinical dementia rating, increased functional difficulties, race, and neuropsychiatric symptoms (depression, agitation, appetite disturbance) were significantly associated with premature exit in the full sample. In the MRI sample, elation, disinhibition, appetite disturbance, and lower hippocampal volume predicted attrition, while motor and sleep disturbance and Hispanic ethnicity predicted study retention. Researchers should utilize the results of baseline psychological, functional, and cognitive assessments to identify targeted retention strategies, while accounting for race, ethnicity, and the reliability of co-participants.